2022
DOI: 10.1590/2317-1782/20212020380
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of smartphone-based hearing screening tests: a systematic review

Abstract: Purpose To verify the accuracy of smartphone apps to identify hearing loss. Research strategies A systematic review followed the PRISMA-DATA checklist. The search strategies were applied across four databases (Lilacs, PubMed, Scopus and Web of Science) and grey literature (Google Scholar, OpenGrey, and ProQuest Dissertations and Thesis). Selection criteria The acronym PIRD was used in review. This included populations of any gender and all age groups. The Index test is the smartphone-based hearing screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
3
1
Order By: Relevance
“…This is marginally higher than the hearX group's published results, which quote 94.4 per cent in an adult population. 1 However, in our sample 8 kHz had a much lower average clinical agreement rate of 71.3 per cent, deeming 8 kHz on hearTest unreliable for diagnosing the severity of hearing loss. Furthermore, hearTest has an average of 97.1 per cent accuracy of diagnosing normal hearing (less than 25 dB) across all of the tested frequencies.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…This is marginally higher than the hearX group's published results, which quote 94.4 per cent in an adult population. 1 However, in our sample 8 kHz had a much lower average clinical agreement rate of 71.3 per cent, deeming 8 kHz on hearTest unreliable for diagnosing the severity of hearing loss. Furthermore, hearTest has an average of 97.1 per cent accuracy of diagnosing normal hearing (less than 25 dB) across all of the tested frequencies.…”
Section: Discussioncontrasting
confidence: 59%
“…Medical health applications offer a huge potential for the improvement of clinical practice and development of how we deliver healthcare to patients. Medical applications have been developed to test for hearing loss, 1 although these are not widely utilised within the National Health Service (NHS) in the UK. Several reports have demonstrated that hearing test threshold values achieved using automated audiometry are similar in reliability compared with results obtained by an audiologist using the conventional manual pure tone audiometry.…”
Section: Introductionmentioning
confidence: 99%
“…This will help future studies to develop PRSs for objective hearing loss. Fast, high-quality hearing applications now make objective data collection more feasible at the population level …”
Section: Discussionmentioning
confidence: 99%
“…Fast, high-quality hearing applications now make objective data collection more feasible at the population level. 43,44…”
Section: Implications Of Findingsmentioning
confidence: 99%
“…When the hearing threshold is not measured, tests to evaluate the hearing of the patient in real-world environments are performed, but, also in these cases, mistakes are common. Finally, few applications have been validated, and, among them, uHear, Audcal, Audiogram Mobile, Hearing Test (e-audiologia.pl), Hearing Test Pro (e-audiologia.pl), HearScreen USA, and hearZA are those most frequently downloaded and used [ 54 ]. The results on their use, despite being generally good, are not uniform.…”
Section: Ear Disordersmentioning
confidence: 99%